Electric transport properties of surface-anchored metal-organic frameworks and the effect of ferrocene loading - Liu, Jianxi; Wächter, Tobias; Irmler, Andreas; Weidler, Peter G.; Gliemann, Hartmut; Pauly, Fabian; Mugnaini, Veronica; Zharnikov, Michael; Wöll, Christof (ACS applied materials & interfaces, 2015)
Understanding of the electric transport through surface-anchored metal-organic frameworks (SURMOFs) is important both from a fundamental perspective as well as with regards to possible future applications in electronic devices. To address this mostly unexplored subject, we integrated a series of representative SURMOF thin films, formed by copper nodes and trimesic acid and known as HKUST-1, in a mercury-drop-based tunneling junction. Although the transport properties of these SURMOFs are analogous to those of hybrid metal-organic molecular wires, manifested by a very low value of the tunneling decay constant (β ≈ 0.006 Å-1), they are at the same time found to be consistent with a linear increase of resistance with film thickness. Upon loading of SURMOF pores with ferrocene (Fc), a noticeable increase in transport current was observed. A transport model and ab initio electronic structure calculations were used to reveal a hopping transport mechanism and to relate the changes upon Fc loading to those of the electronic and vibrational structures of the SURMOF films.
Gesehen am 26.06.2020